Stability and the Economy: Cooperative Game Theoretic Implications for Economic Policy in a Dual-Sector Economy. Issue 2 (19th August 2013) - McDougal, Topher L.
How does the structure of the economy affect the possibility for societal stability? This paper1 employs a cooperative game theory lens to explore possibilities for cooperation and chaos under various growth scenarios and assumptions of distributional equality in a hypothetical 2-sector economy (industrialists and agriculturalists). It suggests that maintaining distributional equality amongst agriculturalists is only undesirable under the assumption that the manufacturing sector exhibits positive and decreasing returns to scale; if increasing or negative manufacturing returns are the case, agricultural equality becomes an important policy goal in maintaining stability. In the particular case of a shrinking economy, peace can be preserved given (a) fairly equitable land distribution, and (b) a healthy industrial sector serving agriculture. In terms of aid policy, I suggest that, under decreasing industrial returns, more resources available to an economy can promote cooperative frameworks, but that such boosts will entail a switch to economies structured around the industrial sector. I conclude with a suggestion for testing the model.